Gestión de inventario en la despensa "Susanita” del cantón Babahoyo - Valle Tualombo, Adriana Madeley (2022)
The work below called Inventory Management in the "Susanita" Pantry begins with the approach to the problem that usually occurs in many commercial companies, in this case in said pantry with respect to its inventory management, which is not performs efficiently thus influencing the productivity of this company. Inventory management is undoubtedly an activity that currently remains little attended by small businesses, however, it must be taken into account that managing the products that are available is essential because the efficiency of the work depends on these. carried out by both the collaborators, as well as the owner of the pantry. For this reason, the objective of this research work is to identify the factors that cause inadequate inventory management in the "Susanita" Pantry. To achieve this objective, theoretical bases were used on the problems observed in this case study, in turn, techniques were applied for the collection of information such as; interview and surveys. The problems that exist in the business were analyzed, the same ones that are detailed in the development of the work. Regarding the methodology, a method was used which is inductive and the types of research, qualitative and quantitative, the techniques were interview and survey, each with its respective questionnaire, in the first instance a diagnosis was obtained that details the inconveniences that occur in the premises in terms of inventory management that has been carried out so far.